Do corruption and political connections drive bank risk-taking behavior? The moderating role of governance across Asian economies - Bekti Ayu Selawati; Rofikoh Rokhim (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Previous studies have examined the effects of corruption and political connections on bank risk taking; however, evidence regarding their effects on banking stability remains inconclusive. This study examines the effects of corruption, political connections, and the role of corporate governance in moderating the relationship between corruption and banking risk, considering the income classification of Asian countries. Methods: This study uses descriptive analysis and random-effects panel regression to examine the effects of corruption, political connections, and corporate governance on bank risk. The sample comprised 95 Asian banks observed from 2019 to 2024. Findings: The results indicate that corruption has a negative and significant effect on banking stability. Corruption increases the risk of bank insolvency. Testing of subsamples of middle-income and high-income countries shows that corruption increases the risk of bank insolvency in middle-income countries but has a different effect on high-income countries’ banks. The positive and significant effect of political connections on bank stability is only observed in middle-income countries. In middle-income countries, governance, proxied by gender composition and educational qualifications, moderates the effect of corruption on the dependent variable. The findings indicate that increasing the proportion of women in the board structure moderates the effect of corruption on banking risk in the sample of banks in middle-income countries. Conclusion: Corruption increases risks in middle-income countries. Political connections and governance variables demonstrate different effects in countries with different income categorization levels. Novelty/Originality of this article: By integrating the variables of corruption, political connections, and corporate governance into banking risk analysis, this study offers a novel contribution while also considering heterogeneity in income levels across countries.